Parameter Assessment of Beam Transport Line for Nuclear Physics Research - Trung, N. V. M.; Smirnov, V. L.; Khiem, Le Hong (Communications in Physics, 2019)
The IBA CP30 cyclotron was installed at the 108 Central Hospital in Hanoi, Vietnam. A proton beam with energy range from 15 to 30 MeV can be delivered by this facility. Currently, facility is mainly used for medical radioactive isotope production. There is an idea to use this accelerator for scientific research as well. For this purpose, a new beam line should be designed. A high energy resolution with minimum momentum spread is a key point for designing. A preliminary design of the beam line using matrix codes, modeling 3D optical elements, magnetic field calculations, and beam dynamics analysis is presented in this paper.